"Posłowie" do niemieckiego wyboru prozy Reymonta - po latach - Zieliński, Jan (Colloquia Litteraria, 2020)
Afterword to the German edition of the selections from the prose of Reymont. After 30 years The article presents the original, hitherto unpublished Polish version of the afterword which Zieliński prepared thirty years ago for the German edition of the selections from Reymont’s prose; it is accompanied by a short introduction. The German version appeared in 1989 in the volume of Reymont’s prose In der Opiumhöhle. Unbekkante Erzählungen, published in West Germany by Suhrkamp in the series ‘Polnische Bibliothek’.